2021
DOI: 10.1111/1365-2435.13911
|View full text |Cite
|
Sign up to set email alerts
|

Litter decomposition affected by bamboo expansion is modulated by litter‐mixing and microbial composition

Abstract: 1. Litter decomposition is a key ecosystem process that drives carbon (C) and nutrient cycling, which could be affected by shifts in plant community composition caused by plant invasion or expansion. However, how changes in leaf litter composition (e.g. litter-mixing effect) and soil microbial community induced by shift in plant community composition affect decomposition remains elusive.2. Here, by deploying 432 litterbags (50μm mesh screen), we treated leaf litter of bamboo Phyllostachys edulis and tree speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…This supports our result that bamboo invasion had a negative effect on surface‐dwelling Collembola. Besides, previous studies have confirmed soil pH increased after bamboo invasion was to increase 20,91,92 ; we further found the increased pH value was significantly related to the decreased abundance of epedaphic Collembola. Such a finding to some extent can be supported by da Silva et al 36 .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This supports our result that bamboo invasion had a negative effect on surface‐dwelling Collembola. Besides, previous studies have confirmed soil pH increased after bamboo invasion was to increase 20,91,92 ; we further found the increased pH value was significantly related to the decreased abundance of epedaphic Collembola. Such a finding to some extent can be supported by da Silva et al 36 .…”
Section: Discussionsupporting
confidence: 72%
“…who found that pH was the main soil parameter that negatively influenced Collembola community. Taken together, bamboo invasion may cause negative shifts in Collembolan community through the regulation of physical and chemical properties of litter inputs and soil 46,51,85,91 . Because the semi‐field experiment is a simplified system, the results cannot be directly extrapolated to the field results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely because the soil organic nutrients provided by the microbial fertilizer treatments were stored in the soil macroaggregates ( Tisdall and Oades, 1982 ), while the soil microaggregates were unable to take up any more microbial residues, resulting in a net loss of microbial residues. After all, small soil aggregates are the primary source of microbial residue buildup ( Luan et al, 2021 ). Moreover, ACF was more effective on soil microbial living and necromass abundances than BMF either alone or in combination in our study ( Table 2 and Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biogeochemical cycles have also been considerably altered by bamboo expansion. For example, bamboo expansion could accelerate the biogeochemical Si cycle [ 11 ], stimulate litter decomposition [ 12 ], and increase soil available P [ 13 ].…”
Section: Introductionmentioning
confidence: 99%